Metals and related substances in drinking water : COST Action 637 :proceedings of the 4th International Conference Metals and Related Substances in Drinking Water, METEAU :Kristianstad, Sweden, October 13-15, 2010 - International Conference Metals and Related Substances in Drinking Water (4th: 2010: Kristianstad, Sweden); Bhattacharya, Prosun; European Cooperation in the Field of Scientific and Technical Research (Organization). COST 637 (London : IWA Publishing, 2012)
Includes bibliographical references.